Postprandial plasma concentrations of glycine and taurine conjugated bile acids in healthy subjects. Issue 3 (March 1983) - Linnet, K
Abstract : Fasting and postprandial plasma concentrations of glycine and taurine conjugates of cholic, chenodeoxycholic, and deoxycholic acid were measured by a high pressure liquid chromatography-enzymatic assay in nine healthy subjects. The mean value of each bile acid concentration increased significantly (2.4-4.7 times) in the postprandial period. The total glycine taurine ratio of 2.5 in the fasting state increased significantly to a maximum value of 3.3 at one to 1 1/2 hours postprandially and then declined. This shift in glycine taurine ratio shows, that the relative increase in concentrations of glycine conjugates exceeds the relative increase in concentrations of taurine conjugates in the early postprandial period, and supports the view that there is significant absorption of glycine conjugated bile acids from the proximal small intestine.